Nitrogen diffusion in the Nb-1.0wt%Zr measured by mechanical spectroscopy - de Souza, Armando Cirilo [UNESP]; Grandini, Carlos Roberto [UNESP]; Florencio, Odila (Trans Tech Publications Ltd, 2008)
The scientific and technological development in the area of new materials contributed to several applications of niobium and its alloys in nuclear power plants as well as in aerospace, aeronautics, automobile and naval industries. This paper presents the interstitial diffusion coefficients of nitrogen in solid solution in the Nb-1.0wt%Zr alloy using internal friction measurements obtained by mechanical spectroscopy, which uses a torsion pendulum operating at an oscillation frequency between 1.0 Hz and 10.0 Hz. The temperature range varies from 300K to 700K, at a heating rate of 1 K/min and vacuum better than 2 x 10(-6) Torr. The results showed an increase of the interstitial diffusion coefficient of nitrogen that was correlated with configurational considerations for the octahedral interstitials.
Keywords: diffusion; Nb-Zr alloys; nitrogen